Phenotypical Characteristics of the Black Yeast Exophiala dermatitidis Are Affected by Pseudomonas aeruginosa in an Artificial Sputum Medium Mimicking Cystic Fibrosis–Like Conditions - Kirchhoff, Lisa; Weisner, Ann-Kathrin; Schrepffer, Mona; Hain, Andrea; Scharmann, Ulrike; Buer, Jan; Rath, Peter-Michael; Steinmann, Joerg (Frontiers in Microbiology, 2020)
Research into the cooperative pathogenicity of microbes in cystic fibrosis (CF) lungs is crucial for an understanding of the pathophysiology of infections and the development of novel treatment strategies. This study investigated the impact of the common CF-associated bacterial pathogen Pseudomonas aeruginosa on the black yeast Exophiala dermatitidis. It evaluated the planktonic growth, biofilm formation, morphology, and virulence of the fungus in the presence or absence of P. aeruginosa. It also determined the role of P. aeruginosa quorum-sensing (QS) molecules within these interactions, e.g., by using sterile culture filtrate and QS-deficient mutants. P. aeruginosa is known to inhibit the planktonic growth of E. dermatitidis. We found that fungal biofilm formation increased in the presence of P. aeruginosa after 24 h but is decreased significantly after 48 h. This effect was reversed when, instead of QS wild-type strains, ΔlasR, and ΔrhlR mutants were added to E. dermatitidis biofilm formation. The number and length of hyphae were substantially reduced when E. dermatitidis was co-cultivated with P. aeruginosa, but not when it was co-cultivated with the mutants. Experiments testing the virulence of E. dermatitidis in the greater wax moth Galleria mellonella showed a synergetic effect on larval killing when E. dermatitidis was injected together with P. aeruginosa culture filtrate. Survival rates were decreased when biofilm culture filtrate was added but not when planktonic culture filtrate was added. In summary, P. aeruginosa affects the growth, morphology, biofilm formation, and virulence of E. dermatitidis. N-acyl-L-homoserine lactone (AHL) QS molecules regulated factors that have been shown to contribute to the inhibition of the ability of E. dermatitidis to form filaments and biofilm.